Computational Insight on CO2 Fixation to Produce Styrene Carbonate Assisted by a Single‐Center Aluminum(III) Catalyst and Quaternary Ammonium Salts. Issue 6 (16th February 2016) - Butera, Valeria; Russo, Nino; Cosentino, Ugo; Greco, Claudio; Moro, Giorgio; Pitea, Demetrio; Sicilia, Emilia
Abstract: DFT calculations were used to investigate the cycloaddition reaction of CO2 to styrene oxide for the formation of styrene carbonate. The uncatalyzed process alongside the reactions assisted by tetrabutylammonium bromide (TBAB), the novel nonsymmetrical single‐center aluminum(III) salen–acac hybrid complex (salenac) (Al1cat) and the binary Al1cat/TBAB system were all investigated and for all of them the optimized structures, rate‐determining steps, and lowest energy barrier reaction pathways were intercepted for both gas‐phase and solvent environments. For the catalyzed systems, the reaction mechanism consists of three key elementary steps: 1) epoxy ring opening; 2) CO2 electrophilic attack and 3) intramolecular cyclization. In the presence of Al1cat, the central metal of the catalyst coordinates with an oxygen atom of the epoxide, activating it towards a nucleophilic attack by the halide. An oxyanion species is formed that affords the corresponding cyclic carbonate after reaction with CO2 . Our results provide important hints on the cycloaddition of CO2 and epoxides promoted by nonsymmetrical aluminum complex containing a single metal center, and can satisfactorily explain the previous experimental observations allowing the development of more efficient catalysts for organic carbonate production. Abstract : Why choose the couple? The cycloaddition reaction of CO2 to styrene oxide for the formation of styrene carbonate is investigated by DFT calculations. The uncatalyzed process as well as the processes catalyzed by tetrabutylammonium bromide, by a nonsymmetrical single‐center aluminum(III) salen–acac hybrid complex, and by the binary system are all investigated for both gas‐phase and solvent environments.